2012
DOI: 10.3329/fmcj.v7i1.10297
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Haemorrhoidopexy Compared with Conventional Haemorrhoidectomy-A Systematic Review

Abstract: Haemorrhoids are one of the most common anorectal disorders. Conventional haemorrhoidectomy (CH) is the most commonly practiced surgical technique. Stapled haemorrhoidopexy (SH) [procedure for prolapsed haemorrhoids (PPH)] is newly developed method for the surgical management of Haemorrhoids. This review looks at the surgical management of prolapsed haemorrhoids in light of this recent development and suggests a treatment approach based on this current evidence. A Medline, Pubmed and Cochrane data base search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The Milligan-Morgan (MM) open haemorrhoidectomy is the most widely practiced surgical technique used for the management of haemorrhoids and is considered the current "gold Standard 9 . Due to the high recurrence rate and potential complications, the use of stapler is decreasing day by day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Milligan-Morgan (MM) open haemorrhoidectomy is the most widely practiced surgical technique used for the management of haemorrhoids and is considered the current "gold Standard 9 . Due to the high recurrence rate and potential complications, the use of stapler is decreasing day by day.…”
Section: Discussionmentioning
confidence: 99%
“…Different study was carried out though out the last 35 years to design a more optimum treatment procedure for haemorrhoid [2][3][4] . The interventional attitude [5][6][7][8] may involve physical and chemical procedures (Mitchell's sclerotherapy, atomization, cryosurgery, infrared, laser or radiofrequency coagulation), supradentate devascularisation (Baron's rubber banding, Pakravan's en Z-haemorrhoidopexy, Morinaga's haemorrhoid arterial ligation, De Longo's stapling haemorrhoidopexy) 9 or haemorrhoidectomies (segmental hemorrhoidectomy of Parks, Milligan-Morgan, Fergusson or their variants using the harmonic scalpel 10 or LigaSure 11 or the radical White head Vercescu's procedure 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The interventional attitude (3,4) may involve physical and chemical procedures (Mitchell's sclerotherapy, atomization, cryosurgery, infrared, laser or radiofrequency coagulation), supradentate devascularisation [Baron's rubber banding, Pakravan's en Z-hemorrhoidopexy, Morinaga's hemorrhoid arterial ligation, De Longo's stapling hemorrhoidopexy (5)] or hemorrhoidectomies [segmental hemorrhoidectomy of Parks, Milligan-Morgan, Fergusson or their variants using the harmonic scalpel (6) or LigaSure (7) or the radical Whitehead-Vercescu's procedure (1)].…”
Section: Background Backgroundmentioning
confidence: 99%
“…In the past years, stapled hemorrhoidopexy became less popular even though early postoperative pain is not as severe as after hemorrhoidectomy [20]. Various studies have shown that PPH is associated with a greater recurrence rate [21], higher stenosis rate [15] when compared with the standard hemorrhoidectomy and it is related with other unusual complications (chronic proctalgia, bleeding granulomatous polyps due to retained staples, rectovaginal fistulae etc.) which are not described after Ferguson or Milligan-Morgan approach [18].…”
Section: Fig 14mentioning
confidence: 99%